ASUHAN KEPERAWATAN PADA NY. D DENGAN DENGUE HEMORRHAGIC FEVER (DHF) DI RUANG AR-ROHIM 1 RUMAH SAKIT RUMAH SEHAT TERPADU DOMPET DHUAFA BOGOR - Beby Alicia Zahra (2022)
Background : Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted from person to person through the bite of the main vector, namely Aedes aegypti, but other species such as Aedes albopictus can also be carrier vectors. This study was conducted to analyze the application of nursing care to Ny. D with Dengue Hemorrhagic Fever (DHF) includes nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. The design used is descriptive using the case study method. The participants used were 1 adult patient with a medical diagnosis of Dengue Hemorrhagic Fever (DHF). Results : Nursing problems that arise in this case are hypovolemia associated with increased capillary permeability, hyperthermia associated with the disease process (DHF), risk of bleeding associated with coagulation disorders (thrombocytopenia). After carrying out nursing actions for 3 x 24 hours, the results of the evaluation of all nursing diagnoses were resolved in accordance with the goals of the established outcome criteria. Conclusion : The application of nursing care to Ny. D with Dengue Hemorrhagic Fever (DHF) achieved the expected results due to good cooperation between nurses, patient families, and other health teams. Keywords : Nursing Care, Dengue Hemorrhagic Fever (DHF), Adults.